Teachers' professional agency in a centralisation-decentralisation system and a hierarchical cultural context: the case of Hong Kong - Lau, Josephine; Vähäsantanen, Katja; Collin, Kaija (Pedagogy, culture & society, 2024)
Teachers are frontline actors in actualising educational innovations. In some contexts, teachers' professional agency is undervalued. This study investigated teachers' agency and its related workplace affordances in Hong Kong, which features a centralised-decentralisation education governance system, and a hierarchical work culture. The study was based on 21 semi-structured interviews with teachers, and employed a deductive thematic analysis. Agency enactment was categorised into 1) pedagogical agency within classrooms, and 2) relational agency in the professional community. The factors contributing to workplace affordances were grouped as pertaining to 1) the collegial community, 2) school leadership, 3) access to resources, and 4) availability of time, space, and job stability. Agency-supportive leadership and a favourable collegial environment significantly facilitated teachers' agentic actions. Teachers did not explicitly resist but implemented emotionally meaningless order in a 'work-to-rule' manner. The study contributes to professional agency research as applied to a particular political, regional, and socio-cultural context.